Optimization study on multicolumn envelope meshing pair of single screw compressor based on leakage characteristics. (August 2018) - Wang, Zengli; Wang, Hao; Qu, Yan; Jiang, Wenchun; Feng, Quanke
Highlights: Theoretical model was built to analyze the effect of MEMP profile parameters. Experiments were carried out to verify the theoretical calculation model. Optimization analyses of the MEMP profile parameters have been put forward. Obtained design principle of envelope columns number, center distance and radius. Abstract: The Multicolumn Envelope Meshing Pair (MEMP) is a significant influence factor of single screw compressor (SSC) performance. It is necessary to carry out an optimization study on MEMP to improve the SSC performance. In this paper, a theoretical calculation model containing three leakage influencing factors is presented to research the influence of the MEMP profile parameters on the leakage characteristics of the SSC. Experiment investigations on the performance of a SSC with MEMP are carried out to verify the theoretical calculation model. With the validated model, the effect of MEMP profile parameters on the leakage characteristics of SSC has been analyzed. Optimization analysis shows that in the design stage more envelope columns with smaller center distance and larger radius should be chosen for the front side of the MEMP, but less envelope columns with smaller center distance and smaller radius should be chosen for the back side of the MEMP.